A bi-functional air electrode developed from a dual-MOF strategy for high-performance zinc-air batteries - Arafat, Yasir; Azhar, M.R.; Zhong, Yijun; Xu, Xiaomin; Tadé, Moses; Shao, Zongping (2024)
A durable, high-performing and cost-effective bi-functional catalyst toward oxygen reduction/evolution reactions (ORR/OER) is the key towards the practical application of Zn-air batteries (ZABs). Here, we report a new concept of combining pristine and carbonized MOFs for developing a bifunctional electrocatalyst for ZABs, where the pristine MOF acts as a support for the OER catalysts and the carbonized MOF acts as the ORR catalyst and enhances the electronic conductivity. By electroless NiP-plating over the surface of the Fe-containing 3D MOF (MIL-100), the catalyst shows superior activity for the OER, delivering a current density of 10 mA cm−2 at an overpotential of 295 mV together with a low Tafel slope of 62 mV dec−1. A 3D porous MOF serves as a substrate for growing NiP with maximal exposed active sites and the iron in the MOF interacts with NiP to further boost the intrinsic OER activity. Subsequently, we introduce carbonized ZIF-67 (C-ZIF-67) into NiP-MIL-100 to build a bifunctional catalyst, where C-ZIF-67 not only provides ORR catalytic activity but also creates a synergetic effect with NiP-MIL-100, and to expedite the charge/mass transfer. Using this air electrode for ZABs, an excellent bifunctionality with a small potential gap (0.78 V), a high peak power density (203 mW cm−2) and robust cycling over a period of 500 h were achieved.